2022
DOI: 10.30935/cedtech/11481
|View full text |Cite
|
Sign up to set email alerts
|

The Increasing Quest for Instructional Designers and Technologists in Higher Education and Corporate Settings

Abstract: As recognition of the roles and contributions of Instructional Design and Technology (IDT) professionals has increased, so has the demand for their skills in the workplace whether in higher education institutions or business entities. However, there remains some ambiguity, especially in higher education, about who IDTs are and what they do. There are also questions about who is hiring them. This content analysis study of 250 advertised higher education and corporate IDT positions found no fewer than 9 job titl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…The rapid prototyping, project management, technology, and business positioning skills listed in the JAs also hinted that LX designers plan for and manage data, time, quality, and cost. This study supports the ID, technology, and project management skills purported by North et al, 2021;Nworie, 2022;Raynis, 2018. Hence, the JAs suggest LX designers need to be responsive to business needs, use data to inform their designs, and be mindful of effectiveness and efficiencies.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The rapid prototyping, project management, technology, and business positioning skills listed in the JAs also hinted that LX designers plan for and manage data, time, quality, and cost. This study supports the ID, technology, and project management skills purported by North et al, 2021;Nworie, 2022;Raynis, 2018. Hence, the JAs suggest LX designers need to be responsive to business needs, use data to inform their designs, and be mindful of effectiveness and efficiencies.…”
Section: Discussionsupporting
confidence: 80%
“…A replication study with more JAs over a longer timeframe can compare and strengthen the key constructs that emerged in this study across industries. Second, Nworie (2022) shared that employers in the education industry may require different design skills than those of business and industry. Like Schmidt and Huang (2021), this study showed that an LX designer draws knowledge and skills from various disciplines and theories.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations